SESBeacon: Nodo sensor electrónico para alertas tempranas - García-Fallas, Francisco (Instituto Tecnológico de Costa Rica, 2016)
This project was developed at Laboratorio de Sistemas Electrónicos para la Sostenibilidad (SESlab) which is part of the School of Electronic Engineer from the Costa Rican Institute of Technology (ITCR). This laboratory investigates and builds electronic systems that contribute to sustainable development. Given this context, this project aims to resolve that necessity that the SESLab currently faces to have a sensor node for wireless communication with the following characteristics: low cost, low power consumption, versatility, and adaptability to a variety of monitoring applications. Following the specific requirements, the SESbeacon node has been designed and implemented based on generic architecture of sensor nodes for Wireless networks. This was possible by using low power consumption devices and techniques that allowed a better operational autonomy of the node at a low economic cost. It was possible to transmit 3 alert statuses: every 0.5 hour, every hour, and every 2 hours according to the time set up chosen by the user, to a distance longer than 50 meter. To accomplish this, a solution based on a centralized approach was applied with a directed diffusion protocol and a scheme of duty cycle adjustment to diminish the energy requirements which turned out to be 44% more economic than initial budget for the project.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Electrónica, 2016.
Keywords: Sensores; Radiofrecuencia; Microcontroladores; Tecnologías limpias; Comunicación inalámbrica; Sistemas electrónicos; Redes; Tecnología inalámbrica